Why Should We Study Sleep Health in Hospitality and Tourism Education? A Theoretical Perspective. Issue 4 (2nd October 2019) - Chiang, Yu Chih; Arendt, Susan W.; Sapp, Stephen G.; Zheng, Tianshu
ABSTRACT: This study developed and examined a new model based on conservation of resources theory to explore how sleep health interacts with resources (i.e., objects, conditions, energies, personal characteristics), stress, and academic performance. Participants were 654 hospitality or business undergraduates from 6 U.S. universities. We analyzed data using descriptive statistics and structural equation modeling. The results of the study showed that (a) sleep health had a significant but weak effect on student grade point average (GPA); (b) stress had no significant effect on student GPA; and (c) students' major did not moderate the relationships between resources, stress, sleep health, and student GPA. Although sleep health does not seem to be a strong predictor of academic performance, it is suggested that educators not ignore the connection between sleep health and students' academic success and individual health. Theoretical implications are provided to help advance hospitality and tourism education applying conservation of resources theory.